IMPACT OF COVID-19 PANDEMIC ON THE SURGICAL TREATMENT OF GASTRIC CANCER: A 3-YEAR ANALYSIS - Amanda Juliani ARNEIRO; Marina Alessandra PEREIRA; André Roncon DIAS; Ulysses RIBEIRO JUNIOR; Marcus Fernando Kodama Pertille RAMOS (ABCD: Arquivos Brasileiros de Cirurgia Digestiva)
ABSTRACT BACKGROUND: The COVID-19 pandemic has overloaded healthcare systems worldwide. Other diseases, such as neoplasms, including gastric cancer, remained prevalent and had their treatment compromised. AIMS: The aim of this study was to evaluate the impact of the COVID-19 pandemic on the treatment of gastric cancer and adherence to the recommended preoperative COVID-19 screening protocol. METHODS: A retrospective study evaluated patients diagnosed with gastric adenocarcinoma who underwent surgical treatment between 2015 and 2023. RESULTS: A total of 769 patients with gastric cancer were evaluated and organized into two groups: (i) pre-COVID group and (ii) COVID group. The pre-COVID group consisted of 527 patients operated on between 2015 and 2019, and the COVID group consisted of 242 patients from 2020 to 2023. The average number of surgical procedures per year in the pre-COVID group was 105 and 81 in the COVID group. There was a statistically significant difference between ASA classification (p=0.002) and clinical staging (p=0.015), which were worse in the COVID group. We observed an increase in diagnostic surgeries (p=0.026), with an increase in the minimally invasive route (p<0.001). In patients undergoing curative surgery, there was a greater indication for postoperative ICU (p=0.022) and neoadjuvant chemotherapy (p<0.001). There was no difference in 30- and 90-day mortality. CONCLUSIONS: The surgical and oncological outcomes for patients operated on during the pandemic remained uncompromised, even though many presented with more advanced initial stages and poorer clinical performance. High adherence to protocols and a low rate of complications related to coronavirus indicate that surgeries were performed safely during this period.